2020
DOI: 10.1016/j.amjcard.2020.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Venoarterial Extracorporeal Membrane Oxygenation After Surgical Repair of Type A Aortic Dissection

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…The results showed that the combined use of VA-ECMO and IABP could be a feasible and effective strategy for managing postoperative cardiogenic shock in AAD patients, although the in-hospital mortality rate was high. The high mortality rate observed in our study is consistent with previous reports, indicating that postoperative cardiogenic shock in AAD patients is a severe condition with high mortality [ 2 , 4 , 5 , 7 10 ]. However, it is noteworthy that among the six patients who received VA-ECMO plus IABP in the operating room due to difficulty weaning from the CPB, four were successfully weaned from VA-ECMO, and three survived until now with a mean follow-up of 20 months.…”
Section: Discussionsupporting
confidence: 93%
“…The results showed that the combined use of VA-ECMO and IABP could be a feasible and effective strategy for managing postoperative cardiogenic shock in AAD patients, although the in-hospital mortality rate was high. The high mortality rate observed in our study is consistent with previous reports, indicating that postoperative cardiogenic shock in AAD patients is a severe condition with high mortality [ 2 , 4 , 5 , 7 10 ]. However, it is noteworthy that among the six patients who received VA-ECMO plus IABP in the operating room due to difficulty weaning from the CPB, four were successfully weaned from VA-ECMO, and three survived until now with a mean follow-up of 20 months.…”
Section: Discussionsupporting
confidence: 93%
“…VA-ECMO can provide temporary mechanical circulatory support and allow time for etiological treatment (6). Previous studies have shown that the in-hospital mortality of patients who receive VA-ECMO assistance after aTAAD surgery is still high (Table 4) (17)(18)(19)(20). Nevertheless, there have been no randomized controlled studies.…”
Section: Discussionmentioning
confidence: 99%
“…There were 781 patients and 242 variables in the registry from 19 cardiac centers in different European and Arabian countries. The purpose of the registry was to gather data on this mechanical circulatory support treatment from many sites in order to evaluate its efficacy and outcome 1,[9][10][11][12][13][14][15][16][17] . Each participating center collected data and entered them into a Microsoft® Access database.…”
Section: The Pc-ecmo Study Cohortmentioning
confidence: 99%